Dietary flavonoids and nitrate: effects on nitric oxide and vascular function - Bondonno, C.; Croft, K.; Ward, Natalie; Considine, M.; Hodgson, J. (2015)
Emerging evidence highlights dietary flavonoids and nitrate as candidates that may explain at least part of the cardioprotective effect of a fruit and vegetable diet. Nitric oxide plays a pivotal role in cardiovascular health. Components of a fruit and vegetable diet that are cardioprotective, in part through effects on nitric oxide status, could substantially reduce the cardiovascular risk profile of the general population with increased intake of such a diet. Epidemiological evidence suggests that dietary flavonoids and nitrate have a cardioprotective effect. Clinical trials with flavonoid- and nitrate-rich foods have shown benefits on measures of vascular health. While the molecular mechanisms by which flavonoids and nitrate are cardioprotective are not completely understood, recent evidence suggests both nonspecific and specific effects through nitric oxide pathways. This review presents an overview of nitric oxide and its key role in cardiovascular health and discusses the possible vascular benefits of flavonoids and nitrate, individually and in combination, through effects on nitric oxide status.